Advancing biology education through HOTS-based learning on digestive system concepts: A systematic literature review - Tiffany Safitri; Didit Ardianto; Irvan Permana; Surti Kurniasih; Eni Nuraeni (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
Developing higher-order thinking skills—critical thinking, creative thinking, and problem-solving—is essential for preparing students to address complex, real-world problems. This systematic literature review, conducted using the PRISMA 2020 guidelines and qualitative content analysis, explores how HOTS is integrated into teaching the human digestive system in secondary education by addressing three key questions: (1) which HOTS are most frequently developed, (2) which instructional strategies are most effective, and (3) what challenges and opportunities exist in implementation. Fourteen peer-reviewed articles published between 2020 and 2024 were analyzed. Results show that critical thinking is the most emphasized skill, followed by creative and problem-solving abilities. Problem-Based Learning (PBL) emerged as the most widely used strategy (21.4%), with STEM, the discovery learning model, and the contextual teaching learning model contributing significantly. Key challenges include curriculum transitions, limited scaffolding, and uneven student participation. Conversely, opportunities arise from integrating technology, applying real-world contexts, and promoting collaboration. While the search included international databases, most studies meeting the inclusion criteria were authored by Indonesian researchers, which may limit cross-contextual generalization. This review underscores the value of combining student-centered learning models with contextual and technological support to enhance HOTS in biology education.Abstrak. Pengembangan keterampilan berpikir tingkat tinggi—berpikir kritis, kreatif, dan pemecahan masalah—merupakan hal penting untuk mempersiapkan siswa menghadapi permasalahan kompleks di dunia nyata. Studi tinjauan literatur sistematik ini dilakukan berdasarkan pedoman PRISMA 2020 dan menggunakan pendekatan analisis isi kualitatif untuk mengeksplorasi integrasi HOTS dalam pembelajaran sistem pencernaan manusia di jenjang pendidikan menengah, dengan menjawab tiga pertanyaan utama: (1) HOTS apa yang paling sering dikembangkan, (2) strategi pembelajaran apa yang paling efektif, dan (3) tantangan serta peluang apa yang muncul dalam implementasinya. Sebanyak 14 artikel terbitan tahun 2020–2024 ditelaah. Hasil menunjukkan bahwa berpikir kritis merupakan keterampilan yang paling dominan, diikuti oleh berpikir kreatif dan pemecahan masalah. Problem-Based Learning merupakan strategi paling banyak digunakan (21,4%), disusul pendekatan STEM, model discovery learning, dan model contextual teaching learning. Tantangan utama meliputi transisi kurikulum, kebutuhan scaffolding, dan partisipasi siswa yang tidak merata. Di sisi lain, peluang muncul melalui integrasi teknologi, penerapan konteks nyata, dan kolaborasi aktif. Meskipun pencarian dilakukan melalui basis data internasional, sebagian besar artikel yang memenuhi kriteria inklusi ditulis oleh peneliti Indonesia, yang dapat membatasi generalisasi lintas konteks. Kajian ini menegaskan pentingnya kombinasi pendekatan kontekstual, teknologi, dan pembelajaran berpusat pada siswa dalam meningkatkan HOTS di pendidikan biologi.